l - Nurul Haeniah (Jurnalistrendi : Jurnal Linguistik, Sastra dan Pendidikan, 2019)
ABSTRACT: This article conceptually discusses logic and its implementation in learning in collaboration with simple case examples in learning practice. The method in this article is a library method that is studying and collecting data from references that are relevant to the topic. The conclusion of the discussion of logic in learning Indonesian is (1) logic as a way of thinking consists of deductive, inductive, linear, and lateral logic, (2) in learning found circular logic symptoms, and (3) logic is implemented in models and learning strategies in class . Logic needs to be learned because the teacher is a problem-solving model for students through the right way of thinking. KEY WORDS: Logic, Learning, Learning Model